Sports Indices Predicting Sustainability Of Sports Development In Kwara State - Ibraheem Musa Oluwatoyin; Ibraheem Tajudeen Olanrewaju; Davi Sofyan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this research is to find out that the do sport policy, sports infrastructure and sports funding have any significant relative contribution in predicting sustainable sports development in Kwara State. The research method used is descriptive survey research type. The population in this study consisted of 127 sports coordinators and trainers in Kwara State. The sampling technique used purposive sampling. The sample in this study amounted to 112 respondents. The data collection instrument used a self-developed questionnaire and validated by three experts. The reliability retest method was adopted whereby 20 copies of the questionnaire were administered to sports managers in the state of Oyo, two times between two weeks interval and the results of the two were correlated using PPMC and 0.77r was obtained. Data analysis used PPMC and multiple linear regression at an alpha level of 0.05. The results of the study illustrate that the sports index (sports policy, sports infrastructure and sports funding) makes a significant contribution to sustainable sports development in Kwara State, Nigeria. The conclusion is that funds, infrastructure, human resources are important elements for the sustainability of sports development.